Validitas Akad Dalam Perjanjian Lisensi Hak Cipta Di Indonesia - Herdifa Pratama (Universitas Cokroaminoto Yogyakarta, 2022)
The license agreement is the latest form of business agreement that has started to appear in the modernization era. Like a business, a license agreement offers an attractive profit so that it can attract interest from various circles, especially in Indonesia. Business through this license agreement is carried out in the form of cooperation between the parties with certain mechanisms. This is a causality of the need for research on the mechanisms and provisions in this agreement. This study aims to explain the validity of the contract in the license agreement in the realm of Indonesian positive law which regulates this matter. Through technical content analysis, this research finds that the mechanism for licensing agreements on copyrights is carried out through the creation of a written contract. The validity of the license agreement is shown by the mechanism that meets the requirements and the pillars of the contract and applies the principles of the contract into it.